Incidence of xerostomia and effectiveness of oral xyletol in xerostomia management among hemodialysis patients - Srinivasa, Sanjay; Muqbool, Danish (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Xerostomia or dryness of the mouth, is a frequent complaint among patients undergoing chronic haemodialysis (HD). However, its incidence and severity in dialysis populations, particularly in tropical regions like India, remain poorly documented. Xerostomia may contribute to intradialytic weight gain (IWG) by influencing fluid intake behaviours, but its role in this context is unclear. This study is aimed to assess the incidence of xerostomia in dialysis patients and evaluate the effectiveness of oral XYLETOL in its management. Methods: This prospective study included CKD stage 5D patients aged 18-75 years, on dialysis for at least 3 months. Xerostomia was assessed using a validated questionnaire, with scores ≥25 indicating significant xerostomia. Patients consenting to further evaluation were administered oral XYLETOL tablets (2 tablets, three times daily, 2 hours after meals) for four weeks. Xerostomia inventory scores were reassessed after treatment and compared with baseline scores. Secondary assessments included intradialytic weight gain (IWG) and hypotension episodes. Results: The study demonstrated that oral XYLETOL tablets effectively reduced xerostomia symptoms in HD patients with significant scores (≥25). Post-treatment xerostomia scores showed notable improvement compared to baseline. However, no significant impact was observed on IWG, indicating that the benefits were confined to symptom relief rather than on hemodynamic changes. Conclusions: Xerostomia in HD patients has multiple contributing factors, including advanced age, systemic diseases, medication use, fluid intake restrictions and salivary gland fibrosis. Early identification of risk factors is crucial for effective management. While XYLETOL is beneficial for reducing xerostomia.